2007
DOI: 10.1371/journal.pone.0000991
|View full text |Cite
|
Sign up to set email alerts
|

Creatine Monohydrate and Conjugated Linoleic Acid Improve Strength and Body Composition Following Resistance Exercise in Older Adults

Abstract: Aging is associated with lower muscle mass and an increase in body fat. We examined whether creatine monohydrate (CrM) and conjugated linoleic acid (CLA) could enhance strength gains and improve body composition (i.e., increase fat-free mass (FFM); decrease body fat) following resistance exercise training in older adults (>65 y). Men (N = 19) and women (N = 20) completed six months of resistance exercise training with CrM (5g/d)+CLA (6g/d) or placebo with randomized, double blind, allocation. Outcomes included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 79 publications
(106 reference statements)
0
102
1
3
Order By: Relevance
“…Norris et al (2009) reported that CLA contributed to a small decrease in weight (~1 kg) in obese postmenopausal women, while Diaz, Watkins, Li, Anderson, and Campbell (2008) found no effect of CLA (1.8 g/day) on body composition or weight in overweight women on an energy-reduced diet (-500 kcal/day) plus 30 min exercise 5 days/week for 3 months. Conversely, two recent studies have shown small improvements in body composition (~1.2 kg gain in lean tissue vs. controls) in normal-weight young (Pinkoski et al, 2006) and older (Tarnopolsky et al, 2007) adults using CLA (5-6 g/day for 7-24 weeks) and participating in resistance exercise. Finally, there appears to be no effect of CLA on exercise performance (Campbell & Kreider, 2008).…”
Section: Conjugated Linoleic Acidmentioning
confidence: 90%
“…Norris et al (2009) reported that CLA contributed to a small decrease in weight (~1 kg) in obese postmenopausal women, while Diaz, Watkins, Li, Anderson, and Campbell (2008) found no effect of CLA (1.8 g/day) on body composition or weight in overweight women on an energy-reduced diet (-500 kcal/day) plus 30 min exercise 5 days/week for 3 months. Conversely, two recent studies have shown small improvements in body composition (~1.2 kg gain in lean tissue vs. controls) in normal-weight young (Pinkoski et al, 2006) and older (Tarnopolsky et al, 2007) adults using CLA (5-6 g/day for 7-24 weeks) and participating in resistance exercise. Finally, there appears to be no effect of CLA on exercise performance (Campbell & Kreider, 2008).…”
Section: Conjugated Linoleic Acidmentioning
confidence: 90%
“…In contrast, supplementation with a CLA mix (3.0 -3.4 g/d) did not affect bone formation or resorption in healthy lean, overweight, obese men and women (65 -67,174) . A further two studies in young and elderly subjects who completed resistance training in addition to CLA supplementation (6 g/d) also demonstrated no change in bone mineral density and bone mass (154,175) . Brown et al (50) reported no change in bone mineral content when subjects consumed a CLA-enriched diet, although the study duration was only 56 d, an insufficient length of time for observing changes in bone mineral content.…”
Section: Conjugated Linoleic Acid and Bone Healthmentioning
confidence: 94%
“…If there is an increase in creatine intake and creatine stores increase, there is a proportionate increase in plasma creatinine due to the increase in delivery to a pool with a normally functioning nephron. Prospective studies using creatine for up to 5 years in healthy people [47,48,49,50] and those with disease [51,52] have uniformly shown no adverse effects of creatine supplementation on renal function. …”
Section: Creatine Monohydrate Supplementationmentioning
confidence: 99%